STUDY OF CONSUMER ACCEPTANCE ON THE NORI SEAWEED (Gracilaria sp.) WITH THE ADDITION OF CAYENNE PEPPER - Fina Rahmadhani; Sukirno Mus; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis aim of this research is to understand consumer acceptance on the nori seaweed (Gracilaria sp.) with different cayenne pepper concentrations and to find resulting product.The method usedexperimental method, with Completely Randomized Design (CRD) non factorial with 4 levels treatmentP0 (control),P1 (2%), P2 (4%) and P3 (6%). The result of this research showed the most like organoleptic by consumer that P2 treatment(4%) was the best treatment with characteristics: the flavors were a bit salty and quite spicy, brownish green color, crunchy texture,the distinct aroma of chili with moisture value (9,17), ash (22,15%), protein (12,59%), and fat content (0,23%).Keywords: Gracilaria sp.,Cayenne Pepper, Organoleptic, Proximate.